2017
DOI: 10.1364/oe.25.00a338
|View full text |Cite
|
Sign up to set email alerts
|

CMOS-integrated GaN LED array for discrete power level stepping in visible light communications

Abstract: We report a CMOS integrated micro-LED array capable of generating discrete optical output power levels. A 16 × 16 array of individually addressable pixels are on-off controlled through parallel logic signals. With carefully selected groups of LEDs driven together, signals suitable for discrete transmission schemes are produced. The linearity of the device is assessed, and data transmission using pulse amplitude modulation (PAM) and orthogonal frequency division multiplexing (OFDM) is performed. Error-free tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Although the 3-dB modulation bandwidth of a single COTS illuminating LED can be up to several MHz [3,5], it reduces to around 350 KHz for grouped LEDs as illustrated in Fig. 3(a) due to the connections of LEDs and driving transistors, which is in line with the observation in [13,18]. It is intuitive to be observed that the larger group with more LED chips has slightly lower running frequency due to the more LED chips in one group have relatively complex wiring connection with each other which delays the control signal.…”
Section: Frequency Response and Output Linearitysupporting
confidence: 77%
See 3 more Smart Citations
“…Although the 3-dB modulation bandwidth of a single COTS illuminating LED can be up to several MHz [3,5], it reduces to around 350 KHz for grouped LEDs as illustrated in Fig. 3(a) due to the connections of LEDs and driving transistors, which is in line with the observation in [13,18]. It is intuitive to be observed that the larger group with more LED chips has slightly lower running frequency due to the more LED chips in one group have relatively complex wiring connection with each other which delays the control signal.…”
Section: Frequency Response and Output Linearitysupporting
confidence: 77%
“…To be more specific, the quantization error has limited impact on the BER performance, and the results clearly show that a proper quantization resolution may improve the BER. Agreed with the early work of [18] which revealed the performance saturates for highest bit resolution due to the increased nonlinearity, so in our test the properly low 6 bit resolution has the best performance thanks to the larger quantization step space. We also directly present the comparison under different quantization resolutions to intuitively illustrate the experiment results as shown in Fig.…”
Section: Ber Vs Transmission Frequencysupporting
confidence: 55%
See 2 more Smart Citations
“…1(a). In the absence of a DAC, an LED array can be employed to generate an analog signal by aggregating the intensity of individual LEDs, also referred to as digital-to-light conversion (DLC) [5]. In this paper, we demonstrate a DLC technique for PAM similar to [5] for non-line-of-sight RS-based (NLOS) OCC.…”
Section: Introductionmentioning
confidence: 99%